496 The Use of Virtual Trauma Clinics (VTC) In the Assessment of Acute Hand Trauma; A Service Evaluation. (4th May 2021) - Creasy, H; Westley, S; Shah, R; Mistry, R
Abstract: As a UK tertiary referral centre for hand trauma the current COVID outbreak has led to the reconfiguration of trauma services. We evaluate the impact of our newly introduced VTC on our hand trauma service, comparing a cohort of patients who were managed pre-COVID, with our current revised pathway. We carried out a service evaluation of all those patients processed by the VTC over 14 days in April 2020 (n = 184). We collected prospective data on timing of referral to assessment and surgery. This data was compared to a matched period in April 2019 (n = 162). Post VTC there has been a significant reduction in time to clerking and time to surgery (p = < 0.001), with 98.1% being clerked within 1 day of referral. Post VTC 12.9% of patients were discharged directly from VTC, all other patients had definitive treatment in a single trip. VTC has shown a clear benefit to patients with definitive management provided in a single trip in all cases. Whilst we have been able to clerk patients earlier any improvement in time to surgery depends on theatre staffing and availability, which differed in the two cohorts and certainly will as we move forward into normal services.